2020
DOI: 10.3389/fmars.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Marine Litter at Three Stations of the HAUSGARTEN Observatory in the Arctic Deep Sea

Abstract: The deep sea is a major sink for debris; however, temporal changes and underlying mechanisms of litter accumulation on the seafloor remain unclear. Photographic surveys at the long-term ecological research (LTER) observatory HAUSGARTEN, in the eastern Fram Strait, have enabled the assessment of spatial and temporal variability of seafloor litter in the Arctic. Previous studies of time-series data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) reported an increase in litter quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 80 publications
(92 reference statements)
3
40
1
1
Order By: Relevance
“…Items were categorised according to their estimated sizes as small (-<10cm), medium (10≤ x ≤ 50cm) or large (>50 cm) to allow for a comparison of the size distribution of debris items from the sea surface (this study) and the deep seafloor (Bergmann and Klages, 2012;Tekman et al, 2017;Parga Martínez et al, 2020). The minimum size of floating debris recorded by the observers was 1 cm.…”
Section: Categorization Of the Floating Itemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Items were categorised according to their estimated sizes as small (-<10cm), medium (10≤ x ≤ 50cm) or large (>50 cm) to allow for a comparison of the size distribution of debris items from the sea surface (this study) and the deep seafloor (Bergmann and Klages, 2012;Tekman et al, 2017;Parga Martínez et al, 2020). The minimum size of floating debris recorded by the observers was 1 cm.…”
Section: Categorization Of the Floating Itemsmentioning
confidence: 99%
“…However, relatively little is known about concentrations of floating marine debris over vast stretches of the open ocean, especially in remote geographic regions such as the polar oceans (Bergmann et al, 2022). Recent surveys revealed substantial amounts of marine debris on Arctic beaches (Bergmann et al, 2017a;Falk-Andersson et al, 2019;Haarr et al, 2020) and on the deep Arctic seafloor (Parga Martínez et al, 2020). Meanwhile, it has been well established that polar regions have become significantly polluted by plastics and that direct land-based input is only one part of the problem (Bergmann et al, 2017a;Suaria et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common fate of marine microplastics is often claimed to be settling on the sea bed, or suspension in deep water columns. Several studies investigated the settling behavior of individual particles of various polymers in different sizes and shapes, , subject to (controlled) weathering conditions and biofouling . These studies have confirmed that their settling behavior follows semiempirical fluid mechanic laws for fluid drag resistance of objects in relative motion to their ambient fluid (i.e., Newton’s second law, leading to Stokes’ law, though empirically corrected for turbulence generation in the particle’s wake). , However, what complicates the prediction of transport and sedimentation of plastics is their wide variety in sizes and shapes, which is made even more complex due to biofilm formation, fragmentation processes, and heteroaggregate formation, diversifying over time and space.…”
Section: Fate and Weatheringmentioning
confidence: 94%
“…Plastic debris is the main contributor to marine litter and the tendency is for it to grow still more following increases in the production of plastic (367 million tonnes in 2020 as mentioned in Plastics Europe, 2020). Plastics are estimated to account for approximately 73% of the total waste in the ocean, while 8 million tonnes of plastic arrive in the oceans every year (Parga Martıńez et al, 2020). Hohn et al (2020) mention future projections according to which the amount of plastic waste could double by 2050 if no strategies to reduce waste are implemented.…”
Section: Introductionmentioning
confidence: 99%